2020
DOI: 10.2147/jaa.s258594
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anti-IL5 Therapies for Severe Eosinophilic Asthma: Literature Review and Practical Insights</p>

Abstract: Severe refractory asthma (SRA) still has a high economic and social impact, including a reduction in quality of life (QoL), productivity, a greater risk of exacerbations and emergency department (ED) visits. Another major issue is the need of oral corticosteroids (OCS), often due to a poor response to standard therapies or the lack of indication for currently available biological drugs. A thorough understanding of the immunological pathways and eosinophilopoietic processes allows a correct application of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…As an example, the present study reported a high percentage of participants with the eosinophilic phenotype who experienced ≥ 3 asthma exacerbations over a period of 12 months. Anti-IL-5 or anti-IL-5 receptor biologic therapy has been shown to reduce the number of exacerbations in patients with eosinophilic asthma and would therefore likely benefit this patient population [ 38 ]. While biologic therapy is beneficial for patients with eosinophilic asthma, a recent study conducted in Brazil found that many patients with severe asthma were not eligible for approved biologics and that those who were eligible may not be able to access them [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the present study reported a high percentage of participants with the eosinophilic phenotype who experienced ≥ 3 asthma exacerbations over a period of 12 months. Anti-IL-5 or anti-IL-5 receptor biologic therapy has been shown to reduce the number of exacerbations in patients with eosinophilic asthma and would therefore likely benefit this patient population [ 38 ]. While biologic therapy is beneficial for patients with eosinophilic asthma, a recent study conducted in Brazil found that many patients with severe asthma were not eligible for approved biologics and that those who were eligible may not be able to access them [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This also has an impact on the OCS-related complications with a consequent reduction in the related economic costs, thanks to the significant steroid-sparing effect of biologics [2][3][4]. In the field of severe eosinophilic asthma (SEA), two important pharmacological options have been available for a few years, namely mepolizumab and benralizumab, and more recently also dupilumab has become usable [5]. These are effective and safe monoclonal antibodies (mAbs), but for which there have been no head-to-head comparative studies yet.…”
Section: Introductionmentioning
confidence: 99%
“…For this group of patients, treatment with monoclonal antibodies targeting some of the cytokines can significantly improve various clinical outcomes in patients with severe asthma [ 16 ]. Omalizumab (humanized, monoclonal antibody that binds to circulating IgE molecules) was the first approved treatment for patients with allergic asthma, followed by treatments targeting the IL-5 pathway: mepolizumab (monoclonal antibody that binds to IL-5), reslizumab (also a monoclonal antibody that binds specifically to IL-5), and benralizumab (monoclonal antibody that binds directly to the IL-5-receptor α on eosinophils) [ 17 ]. Dupilumab is the most recently approved biological treatment for severe asthma.…”
Section: Biomarkers In Asthmamentioning
confidence: 99%